The Japanese position on the American occupation of Iraq in 2003 - Jauda Sabih Al Maliki , Assist. Prof. Dr. Ali (Basra studies journal, 2026)
This Research analyzes the Japanese stance on 2003 US-led invasion of Iraq, focusing on deconstructing the political, strategic, and legal factors that shaped this position at both the official and popular levels. It also seeks to highlight the nature of Japan's role in Iraq's post-war reconstruction efforts. The research addresses several key themes, beginning with the determinants of Japan's policy toward Iraq, moving through the reasons for its support of the US-led invasion, and concluding with the Japanese public's stance and the positions of Japanese political parties regarding the war. The study concludes that Japan's decision to support the US-led invasion stemmed from strategic shifts in its foreign policy, as it sought to enhance its international standing and secure its economic interests related to oil. The research also reveals that Japanese public opinion was largely opposed to the war, with 60% to 80% of citizens opposing participation in military operations, reflecting the gap between official and public opinion. With regard to the reconstruction of Iraq, Japan has made substantial financial contributions, exceeding five billion dollars, and has sent Self-Defense Forces to assist in reconstruction efforts, reflecting a shift in its foreign policy towards greater involvement in international affairs.